Identifikasi Peran Sektor Unggulan Terhadap Pertumbuhan Inklusif : Studi Empiris dari Provinsi Kepulauan Riau - M. Silahul Mu'min; Misbahol (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2025)
Over the last decade, the Riau Islands Province has demonstrated strong economic growth resilience, driven by three leading sectors: Manufacturing Industry, Construction, and Mining and Quarrying. However, this growth has not inclusively addressed socio-economic issues such as poverty, inequality, and unemployment. This study aims to identify the impacts of these key sectors on inclusive growth in the Riau Islands through panel data regression. Additionally, this study calculates the index of inclusive growth using the Poverty Equivalent Growth Rate (PEGR) method. The results indicate that overall, economic inclusivity levels have not been achieved by districts/cities in the Riau Islands Province during 2015-2022, particularly in the lowest inclusive region of the Anambas Islands. Furthermore, the estimated fixed effects model shows that the Manufacturing Industry, Construction, and Mining and Quarrying sectors have a positive and significant influence on inclusive growth in the Riau Islands Province, underscoring the importance of harnessing sectoral potential to achieve inclusive economic growth.